Gauß-Manin systems of families of Laurent polynomials and A-hypergeometric systems - Reichelt, Thomas; Walther, Hans Ulrich (Communications in algebra, 2019)
In this note we study families of Gauß-Manin systems arising from Laurent polynomials with parametric coefficients under projection to the parameter space. For suitable matrices of exponent vectors, we exhibit a natural four-term exact sequence for which we then give an interpretation via generalized A-hypergeometric systems. We determine the extension groups from the parameter sheaf to the middle term of this sequence and show that the four-term sequence does not split. Auxiliary results include the computation of Ext and Tor groups of A-hypergeometric systems against the parameter sheaf.
Gesehen am 05.09.2019